Workplace Environment And Utilization Of Personal Protective Equipment Among Welders In Sharkia Governorate (Journal of Pharmaceutical Negative Results, 2023)
Background: Good working environment and using of personal protective equipment plays important role in preventing occupational hazards and related problems among welders.. The aim of the study was to assess workplace environment and utilization of personal protective equipment among welders in Sharkia Governorate. Subjects & Methods: Design: A descriptive cross- sectional design was used to conduct this study to achieve the aim of this study. Setting: This study carried out at Al’Ashir min Ramadan City in Sharkia Governorate. Subject: One hundred welders were selected by using a multistage random sample from nine steel industries. Two tools were used to collect data they were: Tool I: An interview questionnaire about: demographic characteristics, work related data, Welders health characteristics, and personal protective equipment. Tool II: Observational checklist about welding safety and workplace environment. Results: 48% of studied welders use personal protective equipment. Additionally, 76% of welders used welding goggles, 8% of them used earmuffs and helmet. Also, 41% of welding workplaces had adequate environment. Conclusion: Less than half of the studied welders were compliance with personal protective equipment and more than two fifths of welders’ workplace had adequate environment. Recommendation: Educational & training programs should be conducted regularly to all welders about importance of using personal protective equipment and first aid, PPE should be available, and further studies in other industries for generalization the study results.